Effect Of ROE, ROA, DER, Dan CR Terhadap Stock Price On The LQ45 Index Of The Indonesia Stock Exchange (IDX) For The 2015-2019 Period - Firdausi Ahli; Rizka Ariyanti (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2023)
Entering the era of globalization, the advancement of innovation and competition in the business world is getting tougher. The capital market is the best way to maintain its reality in the business world. In Indonesia, there is capital market called the Indonesia Stock Exchange. In general, the value of the company is described by the development of the company’s share price in the capital market. The higher the stock price of a company, the higher the value of the company. Before investing their funds, investors perform a ratio analysis on the company’s ability to generate profits. This study aims to determine the effect of Return On Equity, return on aset, Debt to Equity Ratio, dan Current Ratio on Stock prices on the LQ45 index of the Indonesia Stock Exchange (IDX)for the 2015-2019 period, either simultaneously, partially, or dominantly. This study uses quantitative research methods. The research sample was 29 LQ45 manufacturing companies which were obtained by using a sampling technique,namely pusposive sampling. Data analysis was performed by multiple linear regression analysis. The result showed that partially the Return On Equity, Return On Aset, dan Current Ratio variables had an effect, while the Debt to Equity Ratio variable had no effect on stock prices in manufacturing companies LQ45 Indonesia Stock Exchange (IDX). Simultaneously, the Return On Equity, return on aset, Debt to Equity Ratio, dan Current Ratio variables have a significant effect on stock prices with an f table value of 2,43 and a significant level of 0,000 less than 0,05.